2017
DOI: 10.1136/bmjopen-2016-013573
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge and practice of dyslipidaemia management among postgraduate primary care trainees in Malaysia: a cross-sectional study

Abstract: ObjectivesDyslipidaemia is one of the main risk factors for cardiovascular disease, the leading cause of death in Malaysia. This study assessed the awareness, knowledge and practice of lipid management among primary care physicians undergoing postgraduate training in Malaysia.DesignCross sectional study.SettingPostgraduate primary care trainees in Malaysia.Participants759 postgraduate primary care trainees were approached through email or hard copy, of whom 466 responded.MethodA self-administered questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(21 reference statements)
3
8
0
Order By: Relevance
“…Despite inconsistent findings on the relationship between physical exercise and depression, this activity should still be strongly encouraged among medical students as it will also bring other benefits beyond just mental health benefit. 22,23 We also found that Tahajjud prayer practiced were significantly associated with lower odds of having depression (AOR= 0.76, 95%CI=0.66-0.88, p<0.001). There was no previous study done to find the association between Tahajjud prayer and depression.…”
Section: Discussionmentioning
confidence: 50%
“…Despite inconsistent findings on the relationship between physical exercise and depression, this activity should still be strongly encouraged among medical students as it will also bring other benefits beyond just mental health benefit. 22,23 We also found that Tahajjud prayer practiced were significantly associated with lower odds of having depression (AOR= 0.76, 95%CI=0.66-0.88, p<0.001). There was no previous study done to find the association between Tahajjud prayer and depression.…”
Section: Discussionmentioning
confidence: 50%
“…Two main possible reasons for the underutilisation could be due to prescriber factors or individual patient factors. A Malaysian study showed that while the majority of clinicians used dyslipidaemia guidelines, there were wide variation in their practice with some clinicians did not prescribe based on the guidelines [ 41 ]. Furthermore, another study reported a high proportion of therapeutic inertia for LLM (61%), which resulted in lower odds of achieving LDL-c target [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate prescriptions were also observed in a previous study in the United Kingdom where most patients were initiated on statins without global CVD risk assessments, and some overtreatment also occurred in the low-risk patients [ 43 ]. A Malaysian study reported better results where 79.7% of clinicians performed risk-scoring prior to statins prescription [ 41 ]. In order to resolve the possible knowledge gap that could have led to inappropriate LLM use, the results of this study should be conveyed to prescribers via continuous medical education programmes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, overall score of <50% and ≥50% base on median score were graded as (poor and good) for knowledge and (negative and positive) for attitude and perception, respectively. 8 Data were analyzed with Statistical Package for the Social Sciences (SPSS) version 20.0 and continuous variables were presented as mean and standard deviation while categorical variables were expressed as frequencies and percentages. Chi-square and Fisher's exact tests were used to test for association as appropriate.…”
Section: Methodsmentioning
confidence: 99%